LAVANDULA OFFICINALIS UNTUK AROMATERAPI DENGAN TEKNIK BOWLING DAN PENGARUHNYA TERHADAP PENURUNAN NYERI KEHAMILAN TRIMESTER II DAN III - Ari Christina; Tri Utami P (Jurnal Ilmiah Kesehatan Media Husada, 2013)
In pregnancy, mothers often has stomach cramp. This condition is normal and generally, but is not really dangerous. But it can not allowed to happen until feel the pain. Medically, stomach cramp is a contraction in pregnancy, it is physiologies reaction from uterus periodically because the uterus contents of fetus. The contraction is felt from second trimester and generally it is hapenned once. One way in increasing the painful is lavender aromatherapy. From the previous research, it is said that lavender is used to decrease the cholera. This research is done to know the effect of lavender in decreasing the stomach painful of pregnant women. The research design is pre experimental with pre-post test design. The research population is pregnant women in second and third trimester which feel painful in pregnancy and they are being the sample. First the respondents are observed the intensity of stomach painful before they are given the lavender aromatherapy and it is observed again after they are given aromatherapy with bowling technique for about 20 minutes. The research result is analyzed by paired t-test. The analyze result paired t-test is got p = 0.000 < 0.05, the conclusion is H1 is accepted. It means there is an effect of lavender aromatherapy in decreasing stomach painful of pregnant women on the second and third trimester. For the health workers, especially midwives is hoped to give the health education and apply the lavender aromatherapy for pregnant women as one alternative in decreasing stomach painful cramp as long as their pregnancy.